2019
DOI: 10.1371/journal.pone.0212585
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for Small Ruminant Lentivirus full genome characterization revealed the circulation of divergent strains

Abstract: Small Ruminant Lentiviruses (SRLV) include at least 4 viral highly divergent genotypes. Genotypes A and B are widely distributed and genotypes C and E have been recognized in restricted geographic areas. New phylogroups have been identified targeting conserved regions. However, this approach suffers from the potential risk to misamplify highly divergent strains. Pathogenic strains are easily adapted to fibroblastic cells, but non-pathogenic strains isolation may require a different approach. We developed a fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
0
33
0
5
Order By: Relevance
“…Genotype A is the most heterogeneous group and has so far been subdivided into 20 subtypes, A1 to A20 4,8-15 . Two recently published studies have to be noted, one by Olech et al 13 that defines SRLV subtype A18, and the other by Colitti et al 15 that defines SRLV subtypes A18 and A19. In the present study, the SRLVs found by Colitti et al 15 are renamed from ' A18' to ' A19' and from ' A19' to ' A20' .…”
mentioning
confidence: 99%
“…Genotype A is the most heterogeneous group and has so far been subdivided into 20 subtypes, A1 to A20 4,8-15 . Two recently published studies have to be noted, one by Olech et al 13 that defines SRLV subtype A18, and the other by Colitti et al 15 that defines SRLV subtypes A18 and A19. In the present study, the SRLVs found by Colitti et al 15 are renamed from ' A18' to ' A19' and from ' A19' to ' A20' .…”
mentioning
confidence: 99%
“…In the present study, there was homology in the genetic sequences obtained between neonates and their mothers, and a strong relationship with the standard strain CAEV Co as well as with the Brazilian sequences BR CNPC (GenBank accession number EU300976, EU300977, EU300978, EU300979), thus proving that the isolated strains were from SRLV. This relationship is explained by the fact that the studied gene is one of the most conserved regions of the viral genome [7] and has traditionally been used in molecular analyzes [3,6,[8][9][10][11][12]. It should be…”
Section: Plos Onementioning
confidence: 99%
“…Structural (gag, pol and env) and accessories genes (vpr, rev and vif) make up the genome of SRLV [6]. Among these, the gag gene is one of the most conserved regions of the viral genome [7], and worldwide it is the target of molecular analysis [3,6,[8][9][10][11][12], allowing to properly characterize the circulating strains in the infected animal's organism due to its ideal minimum genetic variability, compared to other conserved regions of the genome [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are distributed worldwide and mainly spread through animal trade. Within A and B genotypes, specific diseases of sheep and goat are associated to particular subtypes (Colitti et al, 2019;Minguijón et al, 2015). Genotypes C and E have been characterized so far in limited geographical areas (Gjerset et al, 2007(Gjerset et al, , 2006Grego et al, 2007).…”
Section: Introductionmentioning
confidence: 99%